Construction of a comprehensive evaluation model for old community renewal in Suzhou based on smart city concepts - Zhihong Liu; Jilong Chen; Qingyu Wang (Frontiers of Architectural Research)
Rapid urbanization in China presents complex challenges for urban development, particularly in older neighborhoods. The rise of digital cities and the shift from expansion to optimizing existing urban areas have highlighted significant issues related to infrastructure, regeneration, and the preservation of local characteristics. These challenges hinder sustainable urban development and negatively impact residents' quality of life, making the transition to smart cities imperative. This study uses Suzhou's old neighborhoods as a case study, employing big data and Geographic Information System (GIS) software to conduct a comprehensive quantitative assessment. Techniques such as kernel density and accessibility analysis reveal key issues in infrastructure, sustainability, and local characteristics, providing a data foundation for targeted strategies. Based on these findings, the paper proposes micro-renovation strategies aimed at enhancing community functionality and improving residents' quality of life through refined management. The study underscores that, under the “ecological + digital” sustainable development framework, renewing old neighborhoods can address existing challenges while revitalizing cities towards smarter, greener, and more livable futures.